Nuptial symbolism in Second Temple writings, the New Testament, and Rabbinic literature : divine marriage at key moments of salvation history - Villeneuve, André (Assistant Professor of Theology) (Ancient Judaism and Early Christianity, 2016)
In Nuptial Symbolism in Second Temple Writings, the New Testament and Rabbinic Literature , André Villeneuve examines the ancient Jewish concept of the covenant between God and Israel, portrayed as a marriage dynamically moving through salvation history. This nuptial covenant was established in Eden but damaged by sin; it was restored at the Sinai theophany, perpetuated in the Temple liturgy, and expected to reach its final consummation at the end of days. The authors of the New Testament adopted the same key moments of salvation history to describe the spousal relationship between Christ and the Church. In their typological treatment of these motifs, they established an exegetical framework that would anticipate the four senses of Scripture later adopted by patristic and medieval commentators.